Desymmetrization of dicationic diboranes by isomerization catalyzed by a nucleophile - Schön, Florian; Greb, Lutz; Kaifer, Elisabeth; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2020)
Cationic monoboranes exhibit a rich chemistry. By constrast, only a few cationic diboranes are known, that all are symmetrically substituted. In this work, the first unsymmetrically substituted dicationic diboranes, featuring sp2-sp2-hybridized boron atoms, are reported. The compounds are formed by intramolecular rearrangement from preceding isomeric symmetrically substituted dicationic diboranes, a process that is catalyzed by nucleophiles. From the temperature-dependence of the isomerization rate, activation parameters for this unprecedented rearrangement are derived. The difference in fluoride ion affinity between the two boron atoms and the bonding situation in these unique unsymmetrical dicationic diboranes are evaluated.